ANALISIS GAP BIDANG SUMBER DAYA MANUSIA (SDM) RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA UNIT II MENUJU RS TIPE B - Zuhrida Emra Noor; Qurratul 'Aini (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2015)
Background : Issues of ASEAN Free Trade Area ( AFTA ) and globalization of the world economy demands which is every profit and non-profit organizations to compete in marketing and resource. The changes, requires hospitals to survive among competitors that would appear at any moment. Therefore , Human Resources (HR) hospitals must be able to respond it. HR needs proper planning in accordance with the service requirements of each unit in accordance with the classification of hospitals based on the Regulation of the Minister of Health ( Permenkes ) number 56 of 2014 as well as national accreditation standard version of the Commission on Accreditation of Hospitals 2012 ( KARS ). So the RS PKU Muhammadiyah Yogyakarta Unit II will head the hospital type B and accreditation .Methods: The study design was qualitative used in-depth interviews and quantitative method for analyzing a plan about between condition HR today and the need for hospital accreditation of type B and KARS version 2012. While quantitative data obtained through questionnaires Need Assessment journal guidelines on Managerial Competency Development at Provincial and District HospitalsResults : Based on the research results, there is a shortage of human resources about the type and number according to hospital type B and for the accreditation of 99 elements document ratings are 96 % complete . As for performance assessment PKU Muhammadiyah Yogyakarta Unit II responsibility for the examination and treatment, training, science and research, issues of hospital management which is indispensable. To support the referral level, in terms of both treatment and prevention. As well as for international cooperation needs to be improved. While the assessment of training needs at the level of priority on the entire item, respondents give a high priority level assessment.Conclusion : There is a shortage of the type and quantity of human resources between the condition of human resources today and the provisions of hospital type B and there are some completeness of documents for the accreditation of qualifications assessment and education staff KARS 2012 version. Keywords : hospital type B, Permenkes 56/2014, accreditation of KARS version 2012, human resources.